Global research trends and emerging hotspots in nano-drug delivery systems for lung cancer: a comprehensive bibliometric analysis (1998–2024) - Cao Yu; Chong-Qi Fan; Yao-Xuan Chen; Feng Guo; Hao-Han Rao; Peng-Yu Che; Chun-Jian Zuo; Huan-Wen Chen (Discover Oncology)
Abstract Purpose Nano-drug delivery systems (NDDS) have become a promising alternative and adjunctive strategy for lung cancer (LC) treatment. However, comprehensive bibliometric analyses examining global research efforts on NDDS in LC are scarce. This study aims to fill this gap by identifying key research trends, emerging hotspots, and collaboration networks within the field of NDDS and LC. Methods A total of 2452 publications, spanning from 1998 to 2024, were extracted from the Web of Science Core Collection. The data were analyzed using tools such as VOSviewer, CiteSpace, and the R package ‘bibliometrix’. Results The analysis covered contributions from 12,539 researchers affiliated with 2689 institutions across 55 countries, with their work published in 551 different journals. Research output has increased steadily, with China and the United States leading in both publication volume and impact. Major contributors include the Chinese Academy of Sciences and Shanghai Jiao Tong University. The International Journal of Nanomedicine published the most articles, while Journal of Controlled Release ranked highest in co-citations. Kamal Dua authored the most papers, and Maeda, H. was the most frequently co-cited author. Key research areas encompass “active targeting”, “drug delivery optimization”, “overcoming drug resistance”, “nanocarriers”, and “pulmonary drug delivery”. Emerging hotspots include “epithelial mesenchymal transition”, “mucus penetration”, “lipid nanoparticles”, “hydrogels”, and “immune checkpoint inhibitors”. Conclusion This bibliometric analysis, the first comprehensive study on NDDS in LC, identifies China and the United States as leading contributors in publication volume and impact. Key research areas include “active targeting” and “drug delivery optimization”, with emerging hotspots such as “lipid nanoparticles” and “immune checkpoint inhibitors”. These findings provide essential insights to guide future research and optimize treatment strategies.